Big data analytics in the insurance market - Sood, Kiran; Balusamy, Balamurugan; Grima, Simon; Marano, Pierpaolo (Emerald Publishing Limited, 2022)
Big Data Analytics in the Insurance Market is an industry-specific guide to creating operational effectiveness, managing risk, improving financials, and retaining customers. This book will be a 'must' for people seeking to broaden their knowledge of big data concepts and their real-world applications, particularly in the field of insurance. The insurance industry is largely dependent on data, and the advent of Big Data and analytics represents a major advance with tremendous potential. Yet clear, practical advice on the business side of analytics is lacking. This book fills the void with concrete information on using Big Data in the context of day-to-day insurance operations and strategy. This book an invaluable resource for any insurance professional from practitioners and policymakers working at insurance companies, to undergraduate and graduate students of economics management, and finance. Providing high quality academic research, ESFIRM provides a platform for authors to explore, analyse and discuss current and new financial models and theories, and engage with innovative research on an international scale.
Keywords: Insurance -- Data processing.; Insurance companies -- Data processing.; Big data.; Business & Economics -- Insurance -- General.; Insurance & actuarial studies.; elektronické knihy; electronic books